Efeito da intervenção remota realizada pelos pais, direcionado à tarefa motora específica, participação, enriquecimento ambiental e interação mãe-filho (protocolo STEP) sobre a funcionalidade de lactentes com risco biológico: ensaio clínico randomizado controlado - Lima, Camila Resende Gâmbaro (2024)
The main objective of this PhD dissertation was to verify the effect of a telehealth protocol carried out by parents, involving motor stimulation of specific tasks, environmental enrichment, mother-child interaction and participation on the functionality of infants at biological risk. In order to answer the question of this main objective, five studies were developed. Study I consisted of an analysis of the feasibility of applying the Alberta Infant Motor Scale (AIMS) remotely, in a home environment. 30 infants aged 3 to 10 months, with biological risk for developmental delay, were included. The AIMS was applied using videos recorded asynchronously by parents, with family members instructed by therapists through standardized instructions in booklets and texts. In this study, the quality of remote assessment, inter-examiner reliability and the association between contextual factors and the quality of assessments were analyzed. As a result, a high quality of images was found, of the stimuli performed by the caregiver to elicit motor skills, an adequate physical environment for the evaluations, and excellent reliability between evaluators in all AIMS postures, demonstrating the feasibility of this remote evaluation carried out by the caregiver. In Study II, the STEP protocol was presented, and the objective was to describe in detail all stages of this telehealth protocol carried out by parents, involving specific motor tasks, environmental enrichment, mother-child interaction and participation for infants at risk of developmental delay. Thus, all stages and details of evaluation, intervention, randomization, recruitment and blinding were described, to guarantee the reproducibility of this intervention. Study III focused on verifying the feasibility and preliminary effects of the STEP protocol. 28 infants at risk of developmental delay were included (14 in the control group and 14 in the experimental group), who completed the 10 weeks of intervention. The therapy for each group was based on the following principles: 1) Control group: guidelines for stimulating motor tasks; 2) Experimental group (STEP Protocol): guidelines for stimulating motor tasks, participation, mother-child interaction and environmental enrichment, with goals established by the parents. The outcomes presented in this study were: motor skills (AIMS); frequency and involvement of participation (Young Children’s Participation and Environment Measure - YC-PEM) and affordances of the home environment (Affordances in the Home Environment for Motor Development – Infant Scale - AHEMD-IS). After the end of the intervention, the change in each outcome was compared between the groups. The protocol showed good feasibility and high acceptance by parents. The STEP group showed significantly higher results after the intervention, regarding the AIMS percentile; frequency and involvement of participation at home, when compared to the control group. No differences were found in relation to AHEMD-IS. In Study IV, the randomized controlled clinical trial was presented. 52 infants at risk of developmental delay were included, who were also randomized into a control group and an experimental group (STEP Protocol). The intervention processes were the same as those carried out in Study III. In addition to the outcomes assessed in Study III, motor skills outcomes were also assessed using the Infant Motor Profile (IMP), mother-child interaction using items based on the Parent-Child Early Relational Assessment and the environmental part of the YC-PEM. After the 10 weeks of intervention, the STEP Protocol group showed a more evident and significant improvement in the AIMS percentile, Adaptability and IMP Performance, and frequency and involvement of participation at home. Finally, Study V aimed to verify which environmental, family and infant factors impacted adherence to the STEP protocol. Adherence to treatment was calculated by summing the total minutes of therapy performed during the 10 weeks, and the predictors were the type of intervention received; AHEMD-IS; maternal age; number of adults in the house; number of children; paternal and maternal education; family income; level of maternal stress, depression and anxiety and AIMS percentile. Through a regression analysis, it was found that lower values of maternal age, number of adults in the house and levels of maternal depression, higher paternal and maternal education, and being part of the experimental group were associated with greater adherence to therapy. Thus, this thesis concludes the positive effects of the STEP protocol on the functionality of at-risk infants. The results suggest the feasibility of assessment and intervention practices delivered via telehealth and reinforce the importance of including biopsychosocial aspects in early intervention, as well as parental involvement.